Energy Aware IoT Routing Algorithms in Smart City Environment - Ekler, Peter; Levendovszky, Janos; Pasztor, Daniel (IEEE access, 2022)
Energy efficiency is one of the key aspects of IoT and Wireless Sensor Networks (WSNs) since the nodes of the network are running on battery power and the lifespan of the system is an important mission-critical parameter. In WSNs, where the energy consumption mainly depends on the radio interface and the transmission protocols, reliable packet forwarding from the source node to Base Station (BS) is crucial. In this paper, we focus on developing new routing algorithms which extend the lifespan of WSNs by achieving optimal energy balancing subject to the criterion that the packets must reach the BS with a predefined probability. We will propose novel two-hop and multi-hop routing algorithms to achieve this objective. The performance of the novel algorithms is compared with the LEACH routing protocol. Extensive simulations prove that the new routing methods are indeed energy efficient, and they are able to meet the predefined reliability criteria as well. The results given in this paper can contribute to reliable communication in IoT or WSN networks and result in lower energy consumption.